Induction of Apoptosis by Ethyl Acetate Fraction of Astragalus membranaceus in Human Non-small Cell Lung Cancer Cells - Apoptosis Induction by Astragalus membranaceus - - Hyun-Ji Park; Shin-Hyung Park (Korean Pharmacopuncture Institute, 2018)
Objectives: The purpose of this study is to investigate the anti-cancer effects of different fractions of Astragalus membranaceus (AM) in human non-small cell lung cancer (NSCLC) cells. Methods: We isolated hexane, ethyl acetate, and butanol fractions from crude ethanol extract of AM. The cell death was examined by MTT assay and trypan blue exclusion assay. Apoptosis was detected by DAPI staining, annexin V-PI double staining and cell cycle analysis. The expression of apoptosis-related proteins and mitogen-activated protein kinases (MAPKs) was examined by western blot. Results: Among various fractions of AM, the ethyl acetate fraction of AM (EAM) showed the strongest cytotoxic effect in NSCLC cells. EAM reduced the cell proliferation in a time- and dose-dependent manner in NSCLC cells. In addition, EAM induced the chromatin condensation, and increased the population of sub-G1 phase and annexin V-positive cells in a time-dependent manner, indicating that EAM induced apoptosis in NSCLC cells. Consistently, EAM enhanced the expression of cleaved caspase-8 and -9, and induced the accumulation of cleaved- poly (ADP-ribose) polymerase (PARP). Among MAPK proteins, only ERK was dephosphorylated by EAM, suggesting that ERK might be related with EAM-induced apoptosis. Conclusion: Our results clearly demonstrate that EAM exhibited anti-cancer effects in NSCLC cells by induction of apoptosis. We provide a valuable evidence which suggests that AM could be a desirable therapeutic option for treatment of NSCLC.